Proceso de atención de enfermería en paciente con colelitiasis: un estudio de caso - Flores Valle, Edith Matilde (2024)
Cholelithiasis is a common condition affecting the gallbladder, characterized by the formation of gallstones due to an imbalance in bile components. Factors such as obesity, a high-fat diet, genetics, and age increase the risk of developing this condition. Nursing care is essential to prevent complications associated with this disease. This case study aims to develop a nursing care plan for a patient with cholelithiasis, using tools for better outcomes. A comprehensive assessment of a 45-year-old female patient diagnosed with cholelithiasis was performed, followed by the implementation of a nursing care plan based on Marjory Gordon functional patterns to assess and improve the patient's quality of life. Interventions focused on addressing constipation, pain, self-care deficit in eating, and decreased activity tolerance. Vital signs were monitored, emotional support was provided, and the patient was educated on the importance of a balanced diet and self-care. The patient showed significant improvement in mobility, diet tolerance, and reduction in postoperative pain. Adherence to an adequate nutritional regimen contributed to the stabilization of her overall health status, highlighting the importance of a personalized approach in the management of cholelithiasis. Implementation of a nursing care plan based on a comprehensive assessment and personalized interventions is crucial to improve outcomes in patients with cholelithiasis. Ongoing education and dietary follow-up are essential to prevent complications and promote recovery. As a result, we obtained an improvement in the patient's condition, with vital signs, pain reduction with VAS 3/10, and an increased ability to perform daily activities.